Comparison of the Performance of Cartomizer Style Electronic Cigarettes from Major Tobacco and Independent Manufacturers. - Monique Williams; Amanda Villarreal; Barbara Davis; Prue Talbot (PLoS ONE, 2016)
OBJECTIVE:This study compared the performance of 12 brands of cartomizer style electronic cigarettes (EC) using different puffing protocols and measured the concentrations of nicotine in each product. METHODS:Air flow rate, pressure drop, and aerosol absorbance were measured using two different protocols, first 10 puffs and a modified smoke-out protocol. RESULTS:First 10 puff protocol: The air flow rate required to produce aerosol ranged between brands from 4-21 mL/s. Pressure drop was relatively stable within a brand but ranged between brands from 14-71 mmH2O and was much lower than the earlier classic 3-piece models. Absorbance, a measure of aerosol density, was relatively consistent between puffs, but varied between brands. With the modified smoke-out protocol, most brands were puffed until 300 puffs. The pressure drop was relatively stable for all brands except three. Absorbance of the aerosol decreased as the number of puffs increased. Although there was some uniformity in performance within some brands, there was large variation between brands. The labeled and measured nicotine concentrations were within 10% of each other in only 1 out of 10 brands. CONCLUSIONS:Over 10 puffs, the cartomizers all perform similarly within a brand but varied between brands. In smoke-out trials, most brands lasted at least 300 puffs, and performed similarly within brands with respect to pressure drop and absorbance. For five brands, products purchased at different times performed differently. These data show some improvement in performance during evolution of these products, but nevertheless indicate problems with quality control in manufacture.